Exploring the Practitioners Perspective on Remote Onboarding in Software Development Organizations - Perpétua, Sueli Pereira; Peternelli, Mateus de Oliveira; Portela, Carlos dos Santos; Souza, Maurício Ronny de Almeida (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
In the software industry, there has been a significant shift from in-person work to remote or hybrid models due to factors such as the COVID-19 pandemic. This has compelled organizations to adapt their work formats. The transition to virtual work has had a notable impact on the recruitment, integration, and training of new hires, giving rise to the concept of “remote onboarding” or “virtual onboarding”. This refers to the process of integrating new employees who are working remotely, involving all stages and interactions through digital platforms and tools. This paper presents a qualitative study conducted through interviews with 20 professionals involved in the onboarding process in software development organizations. The goal is to characterize how the remote onboarding process is carried out in software development organizations. The results revealed several key findings: First, most organizations have institutionalized onboarding processes to some extent. Second, there is a distinct separation between technical and organizational onboarding, with organizational onboarding tending to be more standardized. Third, the primary challenges identified fall into categories related to learning, communication, and personal aspects. Finally, the main facilitator for the onboarding process is the development of an organizational culture of support and collaboration.